PREVALENCE OF BETA-THALASSEMIA TRAIT IN QUETTA CITY, CROSS SECTION STUDY - Muhammad Aziz; Muhammad Anwar (Journal of University Medical & Dental College, 2015)
ABSTRACT: Identifying the prevalence of Beta Thalassaemia and its carriers in the population of Quetta city. METHOD: Rapid methods of screening like Osmotic Fragility Test (OFT),Mean Cell Volume(MCV), Mean Cell Hemoglobin(MCH), Red Blood Cell (RBC) count and Hemoglobin (Hb) estimation was performed on hematology analyzer, For discrimination Shine and Lal formula was used and morphology of erythrocytes were studied. For these fresh venous blood samples were obtained from different blood banks and hospitals of Quetta city. Using cross section method, a total of 570 blood samples were obtained, Among those 59% were male and 41 % were female. RESULT: Prevalence of Beta thalassemia in population of the city was 6.5% in 2012. The median age was 20 years. 72% were male and 27% were females victims. Ethnic group distribution Pathans, Baloch, Hazara, Afghan refugees and miscellaneous were 41%, 30%, 5%, 11% and 14% respectively. Hematological parameters, OFT observation, blood become turbid in all cases, the mean Hb level were not too much high i.e 10.2 g/dl , MCH (mean) was 18.2(pg) , RBC count 5.9 6(10 /L) mean, MCV was 56(ﬂ) ,In microscopic examination, erythrocytes contained high numbers of microcytosis. RBC morphology also show basophilic stippling and hypochromic. CONCLUSION: OFT not statistically tested for discriminating between anemia, Iron deﬁciency and Beta thalassemia. Due to absence of a single pathognomonic ﬁndings that covers all variants there is need of a set of analysis parameter which give reliable and quick results. On the basis of the evidence provided there is a need for immediately implementing proper screening at grass root level as per guidelines issued by the WHO. Further there is the need of law implemented for couples before they are given approval to get married.